PRIOR EXPECTATIONS AND ITS INFLUENCE ON SERVICE SATISFACTION: THE CASE OF PERSONS WITH ORTHOPEDIC IMPAIRMENTS AND THEIR CARE GIVERS AT THE SALVATION ARMY REBILITATION CENTRE AT AGONA DUAKWA IN GHANA. - Y. Avoke, Anita; Abu-Sadat, Rabbi Abu-Sadat; Nyadu Offei, Yaw (IJRDO - Journal of Social Science and Humanities Research, 2017)
Objective: the aim of the study was to investigate the influence of prior expectations on service satisfaction for persons with orthopedic impairments at the Salvation Army Rehabilitation and Orthopedic Center in Ghana. Design: Prior expectations were explored using interview as a method of data collection and adopted the case study design with focus group discussions and in-depth methods defined the data collection process. Method: Ten (10) participants comprised of four caregivers of children with orthopedic impairments between 0-12 years old (M=11; S.D= 7.8) and six persons with orthopedic impairments between the ages of 12-20 years old (M=34; S.D= 0.71) were purposively selected for the study. Findings: Our study found that service provision at the Salvation Army Rehabilitation and Orthopedic Center was underpinned by prior expectations which influenced greatly on their satisfaction. Recommendations: We recommend that service providers should have more insights into the prior expectations of their users to enable them provide services that would cater for clients expectations. In addition, service providers must educate their users to keep their expectations for their children within what is achievable.